ENSURING LEGAL PROTECTION FOR NOTARIES IN THE REPORTING OF SUSPECTED MONEY LAUNDERING ACTIVITIES - Kukuh Tejomurti; Sasmini; Gabriella Irma Monica Siringo Ringo (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The objective of this study is to examine the legal protection afforded to Notaries as reporting parties and the reporting obligation of Notaries in money laundering cases. The context of this research is the conflict between the Notary's obligation to maintain the confidentiality of client information in accordance with notary law and the obligation to report suspicious financial transactions to prevent and combat money laundering. This conflict generates legal uncertainty regarding the boundaries of a Notary's accountability and the legal safeguards that are available to them when they fulfil their reporting obligations. The urgency of this study is derived from the necessity of more defined legal regulations to guarantee legal certainty and protection for Notaries while simultaneously bolstering efforts to combat money laundering. This investigation implements a normative juridical methodology that incorporates conceptual and statutory methodologies. The findings indicate that the regulations necessitating Notaries to submit reports must be prioritised through the application of the lex specialis derogat legi generali principle. Consequently, Notaries who report in good faith and adhere to the relevant legal procedures are entitled to legal protection.